Botswana : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
Botswana's 2003 Article IV Consultation reports that Botswana's core economic database is largely adequate for surveillance, although the quality and timeliness of national accounts and key trade data need to be improved. Financial sector reforms, including a partial privatization of the civil service pension scheme, are an important part of the economic strategy. The increased risk associated with these reforms should be addressed through enhanced supervision of the sector. The authorities are making efforts to strengthen monetary management.